Efektivitas Mobile Health dan Supportive Education untuk Meningkatkan Kepatuhan Manajemen Perawatan Diri Pasien Hipertensi - Botilangi, Vitta Sofianita; Sriyono, Sriyono; Sari, Dianis Wulan (Journal of Telenursing (JOTING), 2023)
This study aims to evaluate the effectiveness of mobile health interventions and supportive education in increasing self-care management compliance in hypertensive patients. The research method used is a literature review through databases, namely Scopus, Science Direct, Web of Science and Sage Journal. The results of 10 research articles report that interventions using mobile technology (m-health) and supportive educational interventions are very effective in increasing medication adherence in hypertensive patients. Conclusion, Interventions using mobile technology (m-health), combined with supportive educational interventions can be applied to increase self-care management compliance in hypertensive patients. Keywords: Supportive Education, Hypertension, Compliance, Mobile Health